Effect of Mie Scattering on Thermochromic Performance of Branched VO2 Prepared by One‐Step Hydrothermal Method. Issue 18 (5th May 2020) - Wang, Xi; Li, Ming; Wang, Qingsheng; Zhang, Jikui; Shi, Jiaming; Lu, Yuan; Li, Guanghai
Abstract : In this work, gram‐scale branched‐VO2 (B‐VO2 ) was synthesized via a mild one‐step hydrothermal route, and the corresponding phase transition, optical and electrical performances of B‐VO2 were investigated. The differential scanning calorimeter (DSC) results revealed the defect mediated phase transition behavior of B‐VO2 . The optical studies demonstrated an analogous negative thermochromic performance of B‐VO2, which was ascribed to the intense Mie scattering effect. While, ball milling treatment was an effective way to restore the regular thermochromic property, and the ball‐milled VO2 (BM‐VO2 ) displayed a 6.3 % increasement of the solar modulation ability. The BM‐VO2 films on flexible PET and PI substrates demonstrated both energy‐saving and UV‐shielding functions. The temperature dependent resistivity displayed about two orders of magnitude change during the phase transition of VO2 . Abstract : Intensive Mie scattering induced anomalous infrared modulation (–2.2 %) of branched VO2 mesocrystal, and a simple ball milling treatment can restore the regular thermochromic property of ball‐milled VO2 with 6.3 % increase of solar energy modulation.